Julo-Julo: A Social Exchange-Based Cooperative Farming System to Enhance Shallot Productivity in West Sumatra - Indeska Putra; Robi Mitra (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
This study aims to determine the agricultural cooperative strategies of the Julo-Julo group for shallot production in Solok, West Sumatra. This study was conducted in 2024 in Lolo Village, Solok Regency. This study was analyzed using George Homan's social exchange theory. This theory explains that social behavior can be understood as a process of exchange between individuals or social groups. The principles of George Homan's social exchange theory include exchange, benefits, costs, balance, and social influence. This study uses a qualitative approach with a descriptive research type. This research will be conducted from September to November 2024. The selection of informants was carried out using purposive sampling techniques. The informants in this study numbered 20 people (5 key informants and 15 regular informants). Data collection was carried out through in-depth interviews, observation, and documentation. The results of this study are: (1) land management strategies, namely using superior seeds and organic fertilizers. The use of superior seeds can affect the growth of plants and harvest yields, while using organic fertilizers can provide many benefits, such as improving soil quality and plant productivity. (2) Financial management strategies, namely, not using a direct payment system and cost management. The payment system used by the Julo-Julo group does not use a direct payment system in the form of money. The payment system they use uses other resources, namely the workforce, to carry out joint land processing. The management of Julo-Julo group costs for farmers in Lolo village is more burdened with preparations before planting, starting from purchasing seeds, plastic mulch, fertilizer, and pesticides. (3) Social management strategy is seen in communication management, time management, and joint risk management.